PHYSICO-MECHANICAL PROPERTIES OF WOOD AND NON-WOOD PLASTER OF PARIS BONDED COMPOSITE CEILING BOARDS - TEMIDAYO EMMANUEL OMONIYI; KAYODE AYODELE AJOBIEWE (Journal of Engineering Studies and Research)
The effects of wood and non-wood fibres reinforcement on the properties of Plaster of Paris were evaluated. The woody and non woody residues were varied in 10, 20, 30, 40, and 50 % of the whole mix while the Plaster of Paris used was in the ratio 100 (control), 90, 80, 70, 60, and 50 %. The mean density of the composite produced is 3250 kg/m3. The mean thickness swelling and water absorption after 2 and 24 hours were 0.84 % and 0.88 %, and 13.8 % and 16.2 % respectively. The MOR and MOE increased with increase in fibre content hence the composite is suitable for indoor applications.